An evaluation of the performance of a green panel in improving air quality, the case study in a street canyon in Modena, Italy. (15th February 2021) - Donateo, Antonio; Rinaldi, Matteo; Paglione, Marco; Villani, Maria Gabriella; Russo, Felicita; Carbone, Claudio; Zanca, Nicola; Pappaccogli, Gianluca; Grasso, Fabio M.; Busetto, Maurizio; Sänger, Peter; Ciancarella, Luisella; et al.
Abstract: The increasing exposure to air pollutants associated with the world-wide process of urbanization is among the most important risk factors for human health. In this context, the development of green infrastructures has gained interest for providing new win-win solutions for improving air quality and urban climate. In the present work, we have characterized an innovative, engineered green infrastructure, the CityTree (CT), in a real urban setting. Abatement rate of priority pollutants (PMx, NOx, black carbon) by a CT unit was determined, during three intensive field campaigns in the city of Modena (Italy). The measurements of the air filtered through the CT (active mode) showed significant reductions in particulate matter concentration: 19–23% for PM10 aerosol mass, 15–20% for PM2.5, 11–13% for PM1, 38% for ultrafine particle number concentration and 17% for black carbon concentration. The measurements in passive mode (with ventilation off) enabled the estimation of the deposition velocities of aerosol particles and gases onto the device surface. The average deposition velocities for PM10 and NOx observed for the CT mosses fall in the range reported in the scientific literature for other types of green surfaces (e.g., grass lawns, hedges). A comparison of the pollutant removal efficiency between passive and active CT mode was performed. The aerosol removal efficiency of the CT resulted from 3 to almost 20 times higher in filtration than in deposition mode, according to the selected aerosol parameter. These results indicate that moss bio-filters can be more effective in removing air pollutants than standard green infrastructures for in situ applications. Graphical abstract: Image 1 Highlights: Effectiveness of an innovative green wall (CityTree) in improving air quality was evaluated. Air pollutants filtration efficiency (up to 38%) was calculated for a CityTree. Air pollutants deposition velocity was measured at the both sides of the CityTree. Active mode (filtration) system is more efficient than passive (deposition) mode.